Dosimetri In-Vivo Pada Pasien Kanker Payudara dan Nasofaring - Nasukha Nasukha; Suseno MS; Santoso Santoso; Jumadi Jumadi (Institut Teknologi Bandung, 2002)
The need of high accuracy in the use of ionizing radiation for cancer treatment called radiotherapy important. Accuracy in radiotherapy dosimetry depends on dosimetry steps. In-vivo dosimetry is a tool to detect accuracy on radiotherapy dosimetry. In-vivo dosimetry for breast and nasopharynx cancers has been done with diode dosimeters in Co-60 teletherapy. For 6 diode detectors the response fluctuated less than 1,3 % with calibration factors between 0.946 to 1.018. It was found that a mean deviation of -8.76 % or underdose occurred between calculation and measurement, for 17 patients for 140 radiation fields of breast and nasopharynx cancer. This result was higher for patients with breast cancer treatment only, which is -12.28 %. For patients with nasopharynx cancer treatment only difference was -6.88 %. The difficulty of treatment techniques on breast cancer was a factor that caused the deviation.